Interest limitation and thin capitalisation rules: an analysis of global practices and learnings for South Africa - Southgate, Ebrahim (Department of Finance and Tax, 2025)
South Africa loses approximately R7 billion a year due to profit shifting by multinational corporations amounting to about 4% of the total corporate income tax receipts. It is estimated that 98% of this tax loss can be directly attributed to the profit shifting schemes of the largest 10% of multinational enterprises. The term ‘profit shifting' refers to the transferring or shifting of profits within a multinational group of companies from a firm in a higher‐tax‐rate country to an associated company in a lower‐tax‐rate country. It can be legitimate to some degree, however this practice by multinationals is increasingly becoming a challenge for tax authorities and governments worldwide. These challenges are particularly difficult for developing countries such as South Africa as the country is more reliant on corporate tax revenues compared to more economically developed countries. The risk of South Africa's tax base eroding due to profit shifting is thus vitally important to address. It is becoming increasingly important for the South African government to protect its tax base from aggressive tax planning along with attempting to alleviate the burden on taxpayers from the administrative costs of complying with the OECD arm's length approach. Therefore, this dissertation undertook a review of South Africa's current and historic fiscal policies to address base erosion and profit shifting through excessive interest deductions. The research conducted aims to consider how various countries across the world have implemented measuresto address excessive interest deductionsso that South Africa may benefit from their lessons learnt. The review has revealed the various methods that countries have applied to address the risk of excessive interest deductions. Many countries implement interest limitation rules that largely align to the OECD BEPS Action 4 recommendations on excessive interest payments. Some countries implement thin capitalisation rules based on fixed financial statement ratios to curb excessive interest. Other countries have followed a combined approach using the OECD BEPS 4 method and thin capitalisation rules. Certain countries also use other tax safe harbours such as circulating an approved arm's length interest rate for cross‐border finance arrangements to encourage compliance and manage excessive interest payments. It was noted that where countries implemented rules in line with BEPS Action 4, the rules were tailored to suit their unique economic and fiscal needs. These distinctive deviations are highlighted within this dissertation. It was also evident that thin capitalisation safe harbour rules continued to be a key element of interest limitation rules as a means to reduce the compliance burden for low‐risk entities. The research reflectsthat a re‐introduction of thin capitalisation safe harbour rules, to address ever‐increasing complexity in the relevant areas of our income tax legislation, would not be contrary to common practice in a number of countries. Drawing on the findings from the research and analysis conducted, it is recommended that the interest limitation rules in South African should be developed further and improved upon. As an example, these developments might include the reintroduction of thin capitalisation safe harbourrules,stronger alignment ofsection 23M of the Act to the best practice guidelines within BEPS Action Plan 4 or the circulation of government approved arm's length interest rates for cross‐border debt financing transactions between connected persons or associated enterprises.